Nitrogen-doped carbon nanotube sponge with embedded Fe/Fe3C nanoparticles as binder-free cathodes for high capacity lithium–sulfur batteries - Yu-Si, Liu; Ma, Chao; Yu-Lin, Bai; Xue-Yan, Wu; Qian-Chen, Zhu; Liu, Xin; Xing-Hua, Liang; Xiao, Wei; Kai-Xue, Wang; Jie-Sheng, Chen (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
Lithium–sulfur (Li–S) batteries as a promising next-generation energy storage device have received increasing attention recently. However, it is still challenging to achieve high sulfur loading and high areal capacity in the cathodes. Herein, we design a composite of carbon-wrapped Fe/Fe3C nanoparticles grown in a carbonized melamine sponge (Fe/Fe3C@N-CNT) as a free-standing conductive framework and host scaffold for sulfur loading. High sulfur content up to 86.9 wt% and overall mass loading as high as ∼14.44 mg cm−2 are achieved in the resultant Fe/Fe3C@N-CNT/S composite. A high discharge capacity of 1359 mA h g−1 is delivered for this Fe/Fe3C@N-CNT/S composite at 0.1C, and 561 mA h g−1 is retained after 150 cycles. The high electrochemical performance of this Fe/Fe3C@N-CNT/S composite is attributed to the synergistic effect of Fe/Fe3C nanoparticles, carbon coating, and N-doped carbon nanotubes in the Fe/Fe3C@N-CNT cathode.